2015
DOI: 10.4093/jkd.2015.16.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Phlegmonous Esophagogastritis in New Onset Type 2 Diabetes

Abstract: Phlegmonous esophagogastritis is a rare bacterial infection that has been reported to result in mortality. The pathophysiology of phlegmonous gastrointestinal infection is unclear, but some predisposing factors are reported. Those include immunocompromised status, alcohol abuse, malignancy and uncontrolled diabetes mellitus. We report two cases of phlegmonous esophagogastritis with newly diagnosed diabetes mellitus. A 26-year-old woman and a 56-year-old woman individually visited our hospital for sore throat, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Kim et al reported that endoscopic drainage, in addition to traditional open surgery, is a feasible treatment option for phlegmonous esophagitis [9]. Several studies have described the benefits of jejunostomy or gastrostomy for early enteral feeding, resulting in better clinical outcomes [3,4,7,10,11]. Without early diagnosis and proper treatment, phlegmonous esophagitis can lead to many complications, such as peritonitis, mediastinitis, empyema, perforation, or sepsis-and even mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al reported that endoscopic drainage, in addition to traditional open surgery, is a feasible treatment option for phlegmonous esophagitis [9]. Several studies have described the benefits of jejunostomy or gastrostomy for early enteral feeding, resulting in better clinical outcomes [3,4,7,10,11]. Without early diagnosis and proper treatment, phlegmonous esophagitis can lead to many complications, such as peritonitis, mediastinitis, empyema, perforation, or sepsis-and even mortality.…”
Section: Introductionmentioning
confidence: 99%